A Novel Multiband Miniature Planar Inverted F Antenna Design for Bluetooth and WLAN Applications - J. M. Jeevani W. Jayasinghe; Disala Uduwawala (International Journal of Antennas and Propagation)
A novel compact planar inverted F antenna (PIFA) optimized using genetic algorithms for 2.4 GHz (Bluetooth) and 5 GHz (UNII-1, UNII-2, UNII-2 extended, and UNII-3) bands is presented. The patch with a shorting pin is on a 20×7×0.762 mm3 substrate, which is suspended in air 5 mm above a 30×7 mm2 ground plane. Genetic algorithm optimization (GAO) is used to optimize the patch geometry, feed position, and shorting pin position simultaneously. Simulations are carried out by using HFSS and a prototype antenna is fabricated to compare the measurements with the simulations. The antenna shows fractional impedance bandwidths of 4% and 21% and gains of 2.5 dB and 3.2 dB at lower and upper bands, respectively.